Analisis Strategi Pemasaran untuk Meningkatkan Jumlah Nasabah PT PNM Cabang Bojongloa Kidul - Tania Septiani; Aris Rinaldi (BADAN PENERBIT STIEPARI PRESS, 2025)
The background of this research is the importance of an effective marketing strategy for PT PNM Bojongloa Kidul 2 Branch in increasing the number of customers in the midst of fierce competition in the microfinance industry. As a financial institution that focuses on empowering MSMEs, PT PNM needs to optimize its marketing strategy to attract and retain customers. The purpose of this study is to analyze the marketing strategy implemented by PT PNM and assess its effectiveness in increasing the number of quality customers. This study uses a qualitative approach with a descriptive method. Data was collected through interviews, observations, and documentation studies, then analyzed by data reduction techniques, data presentation, and conclusion drawn. The results of the study show that community-based marketing strategies, such as direct approaches, word-of-mouth marketing, and specific segmentation of micro-entrepreneurs, have proven to be effective. The number of customers increased from 1,740 in 2022 to 2,867 in 2025, with a high level of customer satisfaction. The conclusion of this study is that the marketing strategy of PT PNM Bojongloa Kidul 2 Branch has succeeded in increasing the number of quality customers through a personal and community-based approach. However, challenges such as lack of public understanding and competition with other institutions still need to be addressed. The suggestions given include increasing socialization, developing digital platforms, and training human resources to maintain the effectiveness of marketing strategies in the future. This research also opens up opportunities for further studies on digital marketing innovations and collaboration between financial institutions in order to expand reach and build public trust in a sustainable manner. In addition, collaboration with local community leaders and consistent use of social media are also recommended to expand the reach of promotions and increase customer loyalty in the long run.